Struve Geodetic Arc – the Decade in the World Heritage List - Urbanas, Saulius; Parseliunas, Eimuntas Kazimieras; Viskontas, Povilas; Puzienė, Rūta; Būga, Arūnas; Anikenienė, Asta; Gečytė, Silvija; Jakubauskienė, Edita (International Conference “Environmental Engineering”, 2017)
Unique scientific project unifying scientitsts of present modern countries: Norway, Sweden, Finland, Estonia, Latvia, Lithuania, Belarus, Ukraine, Moldova, Russia was carried out in the first half of the 19th century. Results obtained for the mentioned period were very accurate especialy considering the size of the project and instruments used for the measurements. Network of triangulation of 2820 km lenght running from Danube mouth till Arctic Ocean also called Struve Geodetic Arc was built and measured in 1816–1852. That was the longest and most accurate measured meridian arc in 19th century which measurements data were used during the century for computing and improving parameters of the Earth elipsoid. Geodetic points of Struve Geodetic Arc were listed to the World Heritage List in 2005. Three points located in Meškonys, Paliepiukai and Gireišiai were commemorated in Lithuania. The Coordinating Committee of Struve Geodetic Arc was created for colaboration, spreading information for wider public, exchange of the best practice for preservation of Struve Geodetic Arc points. Practice, experience and problems related to the World Heritage List objects preservation are presented and analyzed in this publication.